Воспоминания Е.А. Гиляровой о работе цензором и редактором - Simonova Olga (Институт мировой литературы им. А.М. Горького РАН, 2025)
The study of the history of censorship in the USSR attracts a large number of researchers, but publications of censors’ memoirs are not so common. The memoirs of E.A. Gilyarova represent one of the most interesting periods of the Soviet press, i. e. the 1930s. The introductory article to the publication examines the significance of the censors’ memoirs for the history of literature. A brief biographical note is given about Gilyarova, who, being a prominent Bolshevik, an employee of the People’s Commissariat of Education, was repressed in the 1930s. Subsequently, she contributed to the study of the Bolshevik movement’s history by publishing her memoirs and compiling several collections about the participants of the Revolution and the Civil War. In the being publishing memoirs, Gilyarova describes the internal routine of work in Gorlit, (the General Directorate for Literature and Publishing which carried out censorship in USSR), direct interactions with writers. The above episode with the B.A. Lavrenev’s novel “The World in a Piece of Glass” shows how censorship changed the text: subsequently it was reproduced without the final author’s conclusion. Also, Gilyarova remembers how she took off an obscene poem from Nekrasov’s poetry collection. In the narrative about her work at the GIHL, Gilyarova pays the greatest attention to the figure of K.I. Chukovsky. She describes the editorial work on his book about N.A. Nekrasov, tells about the prohibition of Chukovsky’s works at the turn of the 1920s - 1930s. The present text allows us to form a more comprehensive picture of the pre-War development of Soviet literature, to make conclusions about the influence of censorship and editorial interference factors on it and to show this influence on concrete examples.